Financial Sector Reform and Banking Crises in the Baltic Countries. (IMF Working Papers; Working Paper ;, 1996)
Financial sector reform in the Baltic countries is reviewed in light of the banking crises that emerged during the reform period. It is argued that the crises had their roots in the structural deficiencies specific to planned economies and the financial environment that developed before and after these countries regained their independence, thus rendering them largely inevitable. Because of the low level of financial intermediation, however, even the failure of large banks had limited systemic effects and a minor negative impact on output and incomes. The crises slowed down the financial reform process, but brought about a desired consolidation of the banking sector.